2009
DOI: 10.3390/s90201167
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Neolithic Settlements in Thessaly (Greece) Through Multispectral and Hyperspectral Satellite Imagery

Abstract: Thessaly is a low relief region in Greece where hundreds of Neolithic settlements/tells called magoules were established from the Early Neolithic period until the Bronze Age (6,000 – 3,000 BC). Multi-sensor remote sensing was applied to the study area in order to evaluate its potential to detect Neolithic settlements. Hundreds of sites were geo-referenced through systematic GPS surveying throughout the region. Data from four primary sensors were used, namely Landsat ETM, ASTER, EO1 - HYPERION and IKONOS. A ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 21 publications
1
59
0
2
Order By: Relevance
“…Several magoules are located all over Thessaly and can be found within different kinds of vegetation. Due to the intensive cultivation of the land in the past and their low elevation, a major number of them are not clearly visible from the ground [7,8]. Several studies performed in this area have demonstrated the potentials of remote sensing techniques-with varying degrees of success-for the detection of Neolithic tells [7,8,21,22,47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several magoules are located all over Thessaly and can be found within different kinds of vegetation. Due to the intensive cultivation of the land in the past and their low elevation, a major number of them are not clearly visible from the ground [7,8]. Several studies performed in this area have demonstrated the potentials of remote sensing techniques-with varying degrees of success-for the detection of Neolithic tells [7,8,21,22,47].…”
Section: Discussionmentioning
confidence: 99%
“…Detection of buried archaeological features using medium or high resolution satellite imagery is a well-established procedure in archeological research [1][2][3][4][5][6][7][8]. Buried structures may be identified mainly by image interpretation of crop marks [9][10][11] or using semi-automatic techniques [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…These marks are most often not noticeable when viewed from the ground, but can be seen from the air in favorable conditions, especially when highlighted. Identification of archaeological objects is based on the observation of so-called marks / features that appear in terrain relief (shade, snow, flooding) or the resulting changes in the soil structure associated with human activity (vegetation, humidity, temperature, crop, soil and shadow marks, are generally associated with the presence of buried archaeological remains) (Furmanek, 2013), (NSA), (Alexakis et al, 2009). By verifying the objects that affect the terrain, attention should be paid to several factors/marks: flood, snow, soil, vegetation, humidity, shade and temperature (Beck, 2007), (Bewely, 2003).…”
Section: Problem Statementmentioning
confidence: 99%
“…3a). Additionally, object based segmentation techniques were applied to ASTER images and 15 settlements in total of 234 were detected easily (Alexakis, 2009). The computation of the Normalized Difference Vegetation Index (NDVI) was used to highlight the vegetation differences during different periods of time, in an effort to pinpoint any vague indications for the detection of magoules.…”
Section: Land Classification Vegetation Indices Spatial Enhancementmentioning
confidence: 99%